Content analysis of identity challenges in patients with haemophilia: A qualitative study - Roya Dolatkhah; Reza Shabanloei; Hossein Ebrahimi; Mostafa Ghasempour (Nursing Open, 2021)
Abstract Aims Inherited bleeding diseases greatly affect education, working, job, social activities and quality of life. We aimed to discover the sources of identity challenges among patients with Haemophilia. Design The present study has been designed and performed as a qualitative content analysis research. Methods Participants were purposively selected from haemophilia patients referred to our clinic during one year, from March 2018 to April 2019. Data collection was done through semi‐structured, in‐depth interviews using purposeful sampling. Data were analysed based on Granheme and Landman method. The main categories were fear of rejection, losing social roles, discrimination and stigma and marriage breakdown. Results Patients with haemophilia encounter several challenges due to physical and social constraints caused by the disease. Such challenges result in disturbances in the self‐identity of the patients. Conclusion According to the results of this study, the nurses should plan to have attention to the patients with haemophilia, based on more protection and better supports.